IDENTITATEA ROMÂNEASCĂ ÎNTRE REPREZENTATIVITATE, DEFINIRE ȘI DEZIDERATE. DESPRE INSTITUTUL CULTURAL ROMÂN - DANA GLIGA (Revista de Știinţe Politice şi Relaţii Internaţionale, 2020)
The paper presents a short history and the activity of the Romanian Cultural Institute. The Romanian Cultural Institute is the main Romanian institution whose fundamental purpose is to promote, represent, protect the Romanian culture and civilisation abroad and is one of the most representative symbols of the expressiveness of the Romanian spirituality.